A Soft, Fast and Versatile Electrohydraulic Gripper with Capacitive Object Size Detection (Adv. Funct. Mater. 3/2023). (17th January 2023) - Yoder, Zachary; Macari, Daniela; Kleinwaks, Gavriel; Schmidt, Ingemar; Acome, Eric; Keplinger, Christoph
Abstract : Electrohydraulic Bending Actuators In article 2209080, Keplinger and co‐workers demonstrate a new class of multi‐material electrohydraulic bending actuators, enabling soft and reconfigurable grippers with embodied intelligence. They actuate rapidly and conform to their target, allowing fast and damage‐free gripping of irregular, deformable and fragile objects. Each bending actuator can simultaneously be used as a capacitive sensor, enabling real‐time pick verification and object size detection.